Constitution-Based Positive Legislature: A Comparative Study of Indonesia, Bulgaria, and Mexico - Diar, Adithiya; Rahman; Albi Ternando; Kurniawan, Ridha (Limbago: Journal of Constitutional Law, 2026)
This paper examines the increasing tendency of constitutional judges to function as a “positive legislature,” namely by establishing alternative normative standards rather than merely annulling illegal legislation. The paper used a comparative doctrinal methodology to analyze three jurisdictions: Indonesia's Constitutional Court, Bulgaria's Constitutional Court, and Mexico's Supreme Court. The comparison reveals that Indonesia frequently uses conditional rulings with erga omnes effects to effectively establish replacement norms; Bulgaria often mitigates normative vacuums by reviving previous rules and expansive, teleological constitutional interpretation; and Mexico enhances rights protection through the juicio de amparo and the gradual establishment of progressive, binding precedent. Based on these patterns, the article suggests a Constitutionally Guided Positive Legislature (CGPL) model that directs the creation of judicial norms through (i) structured and open normative intervention, (ii) temporary constitutional norms with clear boundaries, (iii) substantial democratic justification, and (iv) a test for the separation of powers. CGPL is meant to keep judicial lawmaking in check, ensuring it remains fair and responsible while also protecting rights, delivering real justice, and keeping democracy alive.